Etude des interactions hôte/virus chez l’huître creuse Crassostrea gigas et son virus Ostreid herpesvirus 1 - Segarra, Amelie (Université de Bretagne-Sud, 2014)
Ostreid herpesvirus type 1 (OsHV-1) can be considered one of the major infectious agents in Pacific oysters, Crassostrea gigas, in France and all around the world. Differences in terms of mortality among infected animals were reported suggesting a genetic basis of the susceptibility to the OsHV-1 infection. In this context, the main objective of this thesis was to understand the interactions between Pacific oysters and OsHV-1, in particular, the molecular basis of the viral cycle. Results showed that the virus is able to replicate in the host regardless of its stage of development or its susceptibility. However, multiplication kinetics is faster in the most susceptible individuals compared to less susceptible ones. After an active replication phase, it would appear that the virus is no detectable in survival individuals. This observation suggests (i) a remission with elimination of the virus or (ii) virus persistence without detectable symptoms. These results highlight the ability of the virus circulating in the host without causing mortality. These individuals can excrete viral particles and interfere with the infection process in the field. Genes that could be involved in antiviral defenses were also identified in Pacific oysters (IFI44, IAP, glypican, …). All these results represent a first contribution to the understanding of OsHV-1 cycle in Pacific oysters, particularly at the molecular level. Le virus ostreid herpesvirus type 1 (OsHV-1), peut être considéré comme un des agents infectieux majeurs affectant les élevages d’huîtres creuses, Crassostrea gigas, en France et dans le monde. Des différences de mortalités ont été observées au sein de cette espèce lors de l’infection virale laissant suspecter une base génétique de la sensibilité à la maladie. Dans ce contexte, l’objectif principal du travail de thèse était de mieux comprendre les interactions entre l’huître creuse et OsHV-1, et plus particulièrement, les bases moléculaires du cycle viral. Les résultats obtenus montrent que le virus est capable de ...